2019
DOI: 10.7554/elife.49223
|View full text |Cite
|
Sign up to set email alerts
|

Deamidation disrupts native and transient contacts to weaken the interaction between UBC13 and RING-finger E3 ligases

Abstract: The deamidase OspI from enteric bacteria Shigella flexneri deamidates a glutamine residue in the host ubiquitin-conjugating enzyme UBC13 and converts it to glutamate (Q100E). Consequently, its polyubiquitination activity in complex with the RING-finger ubiquitin ligase TRAF6 and the downstream NF-κB inflammatory response is silenced. The precise role of deamidation in silencing the UBC13/TRAF6 complex is unknown. We report that deamidation inhibits the interaction between UBC13 and TRAF6 RING-domain (TRAF6RING… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Conversion of glutamine into glutamate by OspI leads to the inhibition of the synthesis of polyubiquitin chain and UBC13/TRAF6, which resulted in inhibiting the activation of NF-κB. Interestingly, deamidation occurs outside the UBC13/TRAF6 interaction, but changing the salt-bridge interaction inhibits regular interaction between UBC13 and TRAF6 [ 188 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of glutamine into glutamate by OspI leads to the inhibition of the synthesis of polyubiquitin chain and UBC13/TRAF6, which resulted in inhibiting the activation of NF-κB. Interestingly, deamidation occurs outside the UBC13/TRAF6 interaction, but changing the salt-bridge interaction inhibits regular interaction between UBC13 and TRAF6 [ 188 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results also uncover the underlying mechanism by which bacterial deamidation of NEDD8 inactivates CRLs. We have previously shown that the deamidation of the E2 enzyme-UBC13 by the Shigella flexneri deamidase -OspI triggers an intramolecular salt-bridge formation, inhibiting its association with the cognate RING E3 ligase -TRAF6 (37). We show here by MD simulations that deamidation at Q40 triggers the formation of an intramolecular salt bridge between E40 and R74.…”
Section: Discussionmentioning
confidence: 63%
“…Surface electrostatic potential analysis of hnRNPA1 RRMs indicates the presence of distinct, oppositely charged surfaces, which suggests the possibility of encounter complex formation through these complementary surfaces . The role of long-range electrostatic interactions in driving the formation of nonspecific encounter complexes during protein–protein association is well-established for folded proteins. Moreover, repulsive interactions between like-charged surfaces of RRMs could prevent the establishment of long-range structural order within condensates and promote “liquid-like” dynamics.…”
Section: Charge-rich Domains Can Influence Phase Behavior Through Non...mentioning
confidence: 99%